Infective Endocarditis in Children in Italy from 2000 to 2015. Issue 3 (3rd March 2016) - Esposito, Susanna; Mayer, Alessandra; Krzysztofiak, Andrzej; Garazzino, Silvia; Lipreri, Rita; Galli, Luisa; Osimani, Patrizia; Fossali, Emilio; Di Gangi, Maria; Lancella, Laura; Denina, Marco; Pattarino, Giulia; et al.
ABSTRACT: Objective : The Italian Society for Pediatric Infectious Diseases created a registry on children with infective endocarditis (IE) hospitalized in Italy. Methods : A cross-sectional survey was conducted on patients hospitalized due to IE in Italian paediatric wards between January 1, 2000, and June 30, 2015. Results : Over the 15-year study period, 47 IE episodes were observed (19 males; age range, 2-17 years). Viridans Streptococci were the most common pathogens among patients with predisposing cardiac conditions and Staphylococcus aureus among those without (37.9% vs. 5.5%, p = 0.018, and 6.9% vs. 27.8%, p = 0.089, respectively). Six of the 7 (85.7%) S. aureus strains were methicillin-resistant. The majority of patients with and without predisposing cardiac conditions recovered without any complications. Conclusion : In Italy, paediatric IE develops without any previous predisposing factors in a number of children, methicillin-resistant S. aureus has emerged as a common causative agent and the therapeutic approach is extremely variable.